Biologija celice: Navodila za laboratorijske vaje za študente študijskega programa Farmacija - Dariš, Barbara; Lipovšek, Saška (University of Maribor Press, 2025)
Cell Biology: Instructions for Laboratory Work for Students of the Pharmacy Study Program. The work is a collection of laboratory exercises for the subject Cell Biology of the Pharmacy study program. The main topics are the study of the characteristics of human cells with a light microscope, histological and histochemical methods for the analysis of human cells, cell ultrastructure, biosynthetic and secretory pathways, cytoskeleton and extracellular matrix, and examples of cells with a specific function. The structure of the selected cell type enables the specific function of this cell. Students should understand this connection between structure and function, which can be recognized at the level of both cells and tissues. The latter allows for a more comprehensive understanding of the functioning of organs and organ systems.